Gestar a escola pública no Rio Grande do Sul : interfaces entre a legislação e a prática - Castelli, Maria Dinorá Baccin (2010)
This research is intended to discuss the Educational Legislation in respect of Gestar Public School in Rio Grande do Sul, based on the principles of Democracy, Autonomy, Participation and Citizenship. The overall goal is to realize, through the interfaces between the principles that guide the Educational Management, as they materialize Educational Policies in regulatory laws from 1969 to 2009. It is understood through the research literature and documents, the interfaces between principles elected as potential drivers of Educational Policy and Legislation in relation to the act of the Public School Gestar Gaucho. As majorettes, No laws appear 5.751/1969 (State System of Education), No. 10.576/1995 (Democratic Management Act), No. 11.695/2001 and New Proposal-2009, which failed to materialize in the form of law, but made an impact front of the Democratic Management Act, which better reflects the presence of principles relevant to an educational management and that this work was chosen as the parameter for the analysis of other laws. Investigating chronologically and historically the political context of preparing the main documents that rules the educational management in Rio Grande do Sul, will be able, through interfaces with the categories of analysis and four principles to observe the progress and or setbacks the laws in relation to the act of gestating a public school in that state